O07-6 Return to work 12 months after kidney transplantation: results of a cohort study in switzerland. (1st September 2016) - Danuser, Brigitta; Simcox, Amira; Studer, Regina; Koller, Michael; Wild, Pascal
Abstract : Background: Return to work (RTW) with or after a chronic disease is not a well understood process, influenced by a variety of personal, work, societal and medical factors. The aim of this study was to identify predictors for RTW at 12 months after transplantation in kidney-transplanted patients applying a bio-psycho-social model. Methods: All kidney patients followed in the Swiss National Transplant Cohort from May 2008 to December 2012, aged 18 to 65 at registration were included in this study. By linking medical data and a psycho-social questionnaire before, 6 and 12 months after transplantation, we analysed the potential influencing factors on being employed 12 months after transplantation of these three dimensions. Results: Overall of the 689 participating patients, 387 (56.2%) worked 12 months after kidney transplantation compared to 58.9% who worked before transplantation. Age, education, self-perceived health (at 6 months post transplantation), a short waiting time for surgery, pre-transplant employment and an organ from a living donor are significant predictors of RTW. Moreover, while self-perceived heath increased after transplantation and time since transplantation in all groups, the depression score decreased only among those employed at 12 months. The main determinant for RTW (OR = 18.6), pre-transplant employment status was associated with sex, age, education, depression and with duration of dialysis. An organ from a living donor (42.1%) was more frequent in younger age-classes, higher education, non-diabetics and was associated with shorter waiting time till surgery. Conclusion: First employment in chronically ill persons should be helped being maintained as being unemployed pre-transplant is by far the single most important determinant of RTW. Second using organs from living donors should be encouraged and planned also for the promotion of RTW. Finally mental and physical health support and shortening of waiting times are other possible action to promote RTW in kidney patients.